Intra-positional and inter-positional differences in agility tests among youth female volleyball players - Dolo, K.; Vrdoljak, D.; Milic, M.; Grgantov, Z. (SportMont, 2023)
In their structure, indoor sports require quick changes of movement direction. Players should possess a high level of ability to change the direction and speed of movement in response to a stimulus, which is one of the major prerequisites for a high level of performance. During a volleyball match, players are involved in different defensive and offensive activities in which agility plays an important role. The aim of this study was to determine the differences between less successful and more successful youth female volleyball players, as well as their inter-positional and intra-positional differences in agility. The study was conducted on a sample of 204 youth female volleyball players whose mean chronological age was 14.11±0.84 years. The players were divided into 5 subgroups according to their playing position (setters, opposite players, passer-hitters, middle blockers, and libero players). The variable sample used to assess agility consisted of 3 tests: Side steps, 9-3-6-3-9 test, and Step-hop test. Methods of data analysis included the determination of metric characteristics for all three agility tests. The analysis of covariance revealed a significant impact of biological age indicators on all agility tests. Furthermore, discriminant analysis of differences showed that more successful volleyball players achieved better results in all three agility tests. High reliability of the test was determined by Cronbach`s Alpha coefficient (0.87-0.96). The results of this study showed a positive effect of agility tests in differentiating less successful and more successful players regardless of their position. More successful players achieved better results than less successful players in all tests. Greater biological maturity and training experience represent great competitive advantage in this age group. The obtained inter-positional and intra-positional differences and the influence of the biological age indicator on inter-positional and intra-positional differences in agility tests imply that higher biological maturity and training experience are great competitive advantages in this age group. The primary goal of training in younger age groups should not be the current success in the competition, but rather the preparation for achieving the best possible results in senior competition.